Lactiplantibacillus plantarum I Induces Gonad Growth in the Queen Scallop Aequipecten opercularis (Linnaeus, 1758) under Conditions of Climate Change - Ines Kovačić; Petra Burić; Iva Čanak; Ante Žunec; Anamarija Panić; Valentina Kolić; Neven Iveša; Jadranka Frece; Mauro Štifanić (Fishes, 2024)
Climate change has presented a serious problem in recent times, which is why a new approach is being sought in terms of aquacultural food quality. In this study, the influence of temperature increase (by 2 °C) and pH decrease (by 0.2) was investigated on the queen scallop, Aequipecten opercularis (Linnaeus, 1758). Furthermore, the effect of a food-enriched diet with the probiotic culture Lactiplantibacillus plantarum I was assessed in climate-changed conditions. Scallops’ morphometric parameters were measured before the experimental setup and after one month of being kept in controlled conditions. Morphometric parameters included the elongation index, compactness index, convexity index, density index, condition index, meat yield, gonadosomatic index, adductor muscle index, and hepatosomatic index. Climate-changed conditions had no effect on the scallop condition index, meat yield, or hepatosomatic index. Nevertheless, the addition of probiotics to their diet had a positive effect on the queen scallops cultivated under conditions of climate change, influencing positive allometry and the increase of the gonadosomatic indices. On the other hand, the same conditions negatively affected the adductor muscle index of the scallops. To conclude, in the context of climate change conditions, queen scallops could be a good organism of choice that can be very well adapted to the changed environmental conditions, especially with the addition of the lactic acid bacteria culture Lpb. plantarum I.